Funeral Processes During the COVID-19 Pandemic: Perceptions Among Islamic Religious Leaders in Indonesia - Nurhayati, Nurhayati (Journal of religion and health, 2021)
Controversies surrounding the handling of corpses have been amplified during the present COVID-19 pandemic. According to Indonesian scholars, certain perspectives driving these controversies inhibit the implementation of health protocols issued by the government. This study comprehensively explores the diverse perceptions and responses of religious leaders regarding COVID-19 funeral management. Participants comprised six scholars from major Islamic religious organizations, two community leaders, and two families representing COVID-19 patients. Furthermore, content analysis was used to analyze the data. The results showed that the religious leaders, all men aged over 50 years, supported the health directives designed to reduce high transmission risk. However, there were substantial disparities in corpse preparation processes, potentially due to organizational beliefs around burial rites. Some religious leaders aligned their protocols with their religious beliefs. Conversely, families of the deceased insisted that the approved protocol for handling corpses went against their religious and cultural values. Therefore, promotion of protocols and coordination among the government, religious leaders, and the community are needed to decrease the misperceptions and misinformation surrounding the new COVID-19 funeral protocols.